Analisis Efektivitas Program Jaminan Hari Tua di Indonesia Dalam Menjamin Kesejahteraan Pensiunan - Usman, Raphaellee Peters Putra; Rasji, Rasji (Peneliti.net, 2025)
This study aims to evaluate the effectiveness of the Retirement Benefit Program (JHT) in Indonesia in ensuring the welfare of retirees. Through an analysis of internal and external factors, this research identifies the challenges and opportunities in implementing the JHT program and its impact on retirees' welfare. This research method employs a qualitative approach by collecting data through literature review and interviews with relevant stakeholders. The results show that program management and administration, government regulations, community participation, and macroeconomic conditions influence the effectiveness of the JHT program. This study provides a better understanding of the factors affecting the success of the JHT program and offers recommendations for further improvement.